The Effects of Environmental Quality, Technological Progress and Aggregate Risk on Green Growth in the Mena Region - Gritli, Mohamed Ilyes; Rahmouni, Oubeid (International Journal of Energy Economics and Policy, 2025)
Green growth (GG) or environmentally adjusted multifactor productivity growth is essential to achieve the dual objectives of economic development and pollution reduction. In this context, very little work has addressed the issue of sustainable development in the MENA region. Therefore, our work studies the impacts of environmental quality, technological progress and aggregate risk on green growth of this region in the aggregate level. Using the autoregressive distributed lag (ARDL) model over the period 1996-2020, the results demonstrate that GG is positively related to R&D expenditure and natural resource rents but inversely associated with aggregate (economic, financial, and political) risks. In the long run, a 1% increase in total risk decreases GG by 0.7%. In contrast, a 1% increase in profits from fossil fuel exports and innovation increases GG by 0.8% and 0.3%, respectively. The impact of renewable energy consumption is positive but not significant on GG. These findings are also confirmed by alternative regressions and offer several policy recommendations.